Fairness and Equity in Public-Private Partnerships: The Case of Airport Infrastructure Development in the Philippines - Villamejor-Mendoza, Maria Fe (Philippine Journal of Public Administration, 2017)
This paper explores an element of fairness in the public-private partnership (PPP) scheme in the Philippines, i.e., procedural fairness, focusing on the airport development of the Ninoy Aquino International Airport (NAIA) 3, using the build-operate-transfer (BOT) policy. It provides the macro context in adopting BOT as a mechanism for PPP in the case at hand and examines the processes, issues, and prospects in fostering the fair, just, and equitable implementation and management of partnership agreements. It concludes with some observations on the fairness and equity in the PPP/BOT policy and practice in the country.
Keywords: public-private partnership, build-operate-transfer, (procedural) fairness, equity, just compensation